Vascular Flora in Public Spaces of Santiago, Chile [Flora Vascular en el Espacio Público de Santiago, Chile] - Castro-Morales, S (Universidad de Concepcion, 2016)
After an extensive two-year long research effort, the results document the diversity of vascular plants that grow in the public spaces of Santiago, Chile. We analyze the taxonomic composition, life-forms and phytogeographic origin of the vascular flora of Santiago and, finally, we compare the results with those of urban areas in the Northern Hemisphere. We identified 508 species, 100 families, and 338 genera. The families that showed the greatest richness were Asteraceae and Poaceae. We found that at least 85.1% of the species are exotic. The life-forms are similarly represented, although chamaephytes and geophytes are poorly represented. We conclude that the composition of the urban flora of Santiago differs from that of most Northern Hemisphere cities, due to the increased presence of exotic species, which is likely a consequence of the historical and cultural patterns of ornamentation. Therefore it is likely that this urban area would be an adverse environment for the establishment and development of native species. © 2016 Universidad de Concepcion. All rights reserved.